2010
DOI: 10.1007/s10578-010-0190-5
|View full text |Cite
|
Sign up to set email alerts
|

Parental Contributions to Child Anxiety Sensitivity: A Review and Recommendations for Future Directions

Abstract: Anxiety sensitivity (AS) is defined as the fear of anxiety-related symptoms (e.g., a fast beating heart) and the consequences that may follow from these symptoms (e.g., a heart attack). Recently, child AS has been examined in relation to parental AS and parental anxiety to elucidate potential parental contributions. Given inconsistent findings to date, this review was intended to identify parental factors that are significant contributors to child AS. Two key findings from this review included the absence of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 39 publications
1
9
0
Order By: Relevance
“…Alternatively, Silverman and Weems (1999) failed to demonstrate a relationship between parent AS and child AS. Overall, the few studies that have examined parental contributing factors to child AS have yielded inconsistent results warranting further research (Francis and Noël 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Alternatively, Silverman and Weems (1999) failed to demonstrate a relationship between parent AS and child AS. Overall, the few studies that have examined parental contributing factors to child AS have yielded inconsistent results warranting further research (Francis and Noël 2010).…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…Of these studies, three have not reported a significant relationship in clinical (Noël, Francis, Brinston, White, & St. John, 2008; Silverman & Weems, 1999 and community samples (van Beek, Perna, Schruers, Muris, & Griez, 2005), and three found that the relationship was conditional in clinical (East, Berman, & Stoppelbein, 2007) and community samples (Drake & Kearney, 2008; Tsao et al, 2005; see Francis & Noël, 2010 for review). For example, Tsao et al (2005) examined the relationship between parent and child anxiety sensitivity in a sample of 244 youth (aged 8–18 years) and their parents.…”
mentioning
confidence: 99%
“…According to Francis and Noël (2010), specifi c patterns of parental behavior may lead to a higher risk of inducing anxiety in off spring than the existence of certain types of disorder in the parents themselves. Children are more exposed to anxiety when their parents' behavior is threatening, hostile or rejecting (Espinosa, 2009;Scher & Stein, 2003).…”
Section: Introductionmentioning
confidence: 99%